TRUST-BASED VILLAGE FINANCIAL GOVERNANCE: TRANSPARENCY, ACCOUNTABILITY, PARTICIPATION, AND VILLAGE FUND SUCCESS - Rachman, Sri Rachmawati; Wellem, Karmila Alamsyah; Hajar, Khaerunnisa Ibnu (Management Department, Faculty of Economics and Business, Universitas Jambi, 2026)
This study examines how transparency, accountability, and community participation shape community trust and how such trust influences the perceived success of village fund management in Konawe Selatan Regency, Indonesia. Using a quantitative survey design, data were collected from 384 village community members and analysed using partial least squares structural equation modelling (PLS-SEM). The findings reveal that transparency, accountability, and community participation significantly enhance community trust, with transparency emerging as the strongest governance predictor. Community trust strongly predicts perceived village fund management success, indicating that citizens evaluate village fund performance not only through administrative compliance or program realization but also through confidence in village government integrity, competence, and responsiveness. The theoretical contribution of this study lies in advancing a trust-based village financial governance perspective by integrating Good Governance Theory, Institutional Trust Theory, and Public Value Theory. This perspective explains how governance practices generate public trust and how trust translates village financial governance into perceived public value. The study provides practical implications for strengthening citizen-friendly transparency, social accountability, and meaningful participation in rural public financial management.